Assessing Young Learners’ Listening and Speaking Performance - Norasiah, Norasiah; Sugirin, Sugirin (EDUPEDIA Publisher, 2023)
This study aims to investigate the types of oral language assessment tasks which is used by the teacher in assessing EYL speaking and listening performance. The national curriculum also decides to introduce English since elementary schools as include in local content subjects. However, some English teachers still find some difficulties in forming the teaching methodology and its assessment. Some debates coming whether English for young learners should concern on productive skills or receptive skills or cover all skills. Besides, some problems also arise from how to assess the young learners since it is as local subject and they also still learn the second language (Indonesian). Therefore, this article concerns on speaking and listening assessment since the writer think that speaking and listening are the key points for young learner to study further